What Determines the Perception of Segmentation in Contemporary Music? - Michelle Phillips; Andrew J. Stewart; J. Matthew Wilcoxson; Luke A. Jones; Emily Howard; Pip Willcox; Marcus du Sautoy; David De Roure; David De Roure (Frontiers in Psychology, 2020)
BackgroundThis study concerns the perception of musical segmentation during listening to live contemporary classical music. Little is known about how listeners form judgments of musical segments, particularly when typical section markers, such as cadences and fermatas, are absent [e.g., Sears et al. (2014)] or when the music is non-tonal (e.g., in much contemporary classical music).AimsThe current study aimed to examine the listeners’ segmentation decisions in a piece of contemporary music, Ligeti’s “Fanfares”?MethodsData were gathered using a smartphone application [Practice & Research in Science & Music (PRiSM) Perception App] designed for this study by the Royal Northern College of Music (RNCM) Centre for PRiSM and the Oxford e-Research Centre. A total of 259 audience participants were asked to “tap” when they felt that a section had ended. Subjective responses were captured, as well as contextual data about the participants.ResultsThe audience members demonstrated high levels of agreement regarding segmentation, mostly at places in the music involving breaks in the musical texture (one piano hand resting), changes in dynamic (volume), and changes in register/pitch. A sense of familiarity with contemporary repertoire did seem to influence the responses—the participants who self-reported being familiar with contemporary music used a wider range of cues to make their segmentation decisions. The self-report data analysis suggested that the listeners were not always aware of how they made decisions regarding segmentation. The factors which may influence their judgment of musical segmentation are, to some extent, similar to those identified by music analysis (Steinitz, 2011) but different in other ways. The effect of musical training was found to be quite small.ConclusionWhether musically trained and/or familiar with contemporary classical music or not, the listeners demonstrate commonalities in segmentation, which they are not always aware of. This study has implications for contemporary composers, performers, and audiences and how they engage with new music in particular.